Variability of Soil Micronutrients Concentration along the Slopes of Mount Kilimanjaro, Tanzania - Mathayo Mpanda Mathew; Amos E. Majule; Robert Marchant; Fergus Sinclair (Applied and Environmental Soil Science)
Soil micronutrients are important elements for plant growth despite being required in small quantities. Deficiency of micronutrients can result in severe crop failure while excess levels can lead to health hazards; therefore, investigating their status in agricultural land is crucial. Fifty plots were established along an altitudinal gradient from 680 to 1696 m a.s.l. on the slopes of Mount Kilimanjaro, Tanzania. Soils were sampled at the top- (0–20 cm) and subsoils (21–50 cm) in four locations within each plot. Fourier Transform Mid-Infrared (FT-MIR) spectroscopy and wet chemistry were used for soil analysis. Results indicated that the mean concentrations of the micronutrients in the topsoil were Fe (130.4±6.9 mgkg−1), Mn (193.4±20.5 mgkg−1), Zn (2.8±0.2 mgkg−1), B (0.68±0.1 mgkg−1), and Cu (8.4±0.8 mgkg−1). Variations of the micronutrients were not statistically different by elevation (df = 41, p>0.05) and by soil depth (df = 49, p>0.05). Correlations among micronutrients were significant for Fe versus Mn (r=0.46, p<0.001), B versus Zn (r=0.40, p=0.003), B versus Cu (r=0.34, p=0.013), and Cu versus Zn (r=0.88, p<0.001). The correlated micronutrients implied that they were affected by similar factors. Soil pH correlated positively with B, Fe, and Mn and negatively with Cu and Zn, hence probably influencing their availability. Therefore, the need for sustaining micronutrient at sufficient levels is crucial. Management interventions may include moderating soil pH by reducing acidity through liming in the higher elevations and incorporation of organic matter in the lowlands.